Concept development assessment game – suitable collecting framework in scientific military research - George-Ion TOROI (Bulletin of "Carol I" National Defense University)
Scientific research is crucial for progress across all areas of society, including the military sphere. However, as the security environment becomes increasingly dynamic, unpredictable, and complex, research methods in military sciences must address contemporary challenges by providing flexible frameworks for evaluating and testing new concepts necessary for the adaptation of force structures. This article analyzes the Concept Development Assessment Game (CDAG), which offers a structured framework for collecting qualitative data in military-specific research. The game serves as a qualitative tool used for testing and refining concepts at an early stage of development, providing a controlled and flexible environment for collecting necessary data. Moreover, it ensures a mechanism for employing a wide range of data collection methods, such as observation, focus groups, or questionnaires, thereby enabling the triangulation of collected data and, consequently, the foundation for valuable outcomes in the effort to transform military structures.